Analyzing the Rendement, Water Content, Chemical and Organoleptic Properties of Watermelon (Citrullus lanatus) Sweet Spicy Seasoning: Seasoning, Sweet spicy, Watermelon. - Siti Sabariyah; Muhammad Jufri; If’all If’all; Siti Fathurrahmi; Spetriani Spetriani; Sultan Sultan; Ramadhani Chaniago (Jurnal Penelitian Pendidikan IPA, 2025)
Until now, the use of watermelon has not been carried out optimally, often watermelon is only used as a food ingredient that is processed in less varied ways. This research aims to determine the physical, chemical, and organoleptic properties of sweet and spicy watermelon sprinkles and determine the physical, chemical, and organoleptic properties of the best sweet and spicy watermelon sprinkles. Sprinkle seasoning can improve taste and aesthetics in the food industry which is practical and varied. This research was carried out using a factorial Completely Randomized Design (CRD) and organoleptic testing with three replications consisting of: Factor A (addition of watermelon) S1=1000g Watermelon, S2= 800g Watermelon, S3= 600g Watermelon, S4= 400g Watermelon. Factor B (storage time,) P0 = no storage, P1 = 2 weeks of storage (P2 = 2nd month of storage for antioxidant testing). The best treatment of 40% was found in the fourth treatment after 2 weeks of storage. The best water content of 17.67% was found in the second treatment after 2 weeks of storage. The best antioxidant activity of 7.96 ppm was found in the first treatment without storage. The best Vitamin C content* both with and without storage was 0.19%. The best organoleptic taste 3.45 was found in treatment 1 without storage, in the aroma test the best and much liked